Survival of multiple-surface ART restorations using a zinc-reinforced glass-ionomer restorative after 2 years: A randomized triple-blind clinical trial. Issue 9 (September 2019) - Mobarak, E.; El-Deeb, H.; Daifalla, L.E.; Ghaly, M.; Mustafa, M.; Sabry, D.; Fatah, H.; Mulder, J.; Creugers, N.H.J.; Frencken, J.E.
Abstract: Objective: To investigate the effectiveness of a new zinc-reinforced glass-ionomer in comparison to a common high-viscous glass-ionomer cement (HVGIC) used in multiple-surface ART-prepared cavities. The hypothesis tested was that the cumulative survival percentage of the new HVGIC is higher than that of the common HVGIC over 2 years. Methods: A randomized triple-blind parallel group clinical trial was used. A total of 218 participants, average age 15.4 years (SD = 0.2), with an occluso-proximal carious lesion in a permanent (pre-) molar were included. Restorations using test (ChemFil Rock) and control (Fuji IX GP) restoratives were placed according to the ART method by four calibrated operators. Restorations were evaluated after one week (baseline), and at 6-, 12-, 18- and 24 months from replicas and coloured photographs according to the ART restoration assessment criteria by two independent evaluators. Restoration survival curves were estimated using the Kaplan–Meier method and difference between dependent and independent variables tested with a Wald (chi-square) test. Results: There was a statistically significant difference in cumulative survival percentages between the two types of restorations at 2 years ( P = 0.02). A higher percentage of multiple-surface restorations of Fuji IX GP (95.4%) than ChemFil Rock (85.3%) survived. Gender ( P = 0.64), operator ( P = 0.56) and cavity size ( P = 0.81) had no effect on the survival of the type of restoration observed. Type of tooth ( P = 0.004) and type of jaw ( P = 0.05) showed an effect. Severe wear was the major reason for restoration failure (ChemFil Rock = 7; Fuji IX GP = 1). Significance: ChemFil Rock appears not to be a viable alternative to Fuji IX GP in restoring ART multiple-surface cavities in permanent posterior teeth.